Development and validation of a monoclonal antibody-based competitive ELISA for detection of antibodies against porcine epidemic diarrhoea virus (PEDV). (December 2018) - Sozzi, Enrica; Moreno, Ana; Lelli, Davide; Perulli, Simona; Prosperi, Alice; Brocchi, Emiliana; Capucci, Lorenzo; Papetti, Alice; Giacomini, Enrico; Alborali, Giovanni Loris; Lavazza, Antonio
Abstract: Porcine epidemic diarrhoea virus (PEDV), belongs to the genus Alphacoronavirus in the family Coronaviridae and causes severe diarrhoea, vomiting, dehydration and high mortality in seronegative newborn piglets. Thus, a precise and rapid diagnosis of PEDV infection is important for the application of control measures to limit viral dissemination. In this investigation, a monoclonal antibodies (MAbs)-based competitive enzyme-linked immunosorbent assay (ELISA) for detecting antibodies against PEDV was developed and validated. The diagnostic performance of the test was evaluated by receiver operating characteristic (ROC) analysis using a panel of 829 known sera collected from different commercial pig farms, with or without a history of PED presence and from experimentally infected pigs. The competitive ELISA showed excellent diagnostic performance and discriminatory power with high sensitivity (Se) and specificity (Sp) values (Se = 96.5%, 95% IC 94.1–98.1; Sp = 98.2%, 95% IC 96.3–99.3). Moreover, this competitive ELISA method has other properties, such as high feasibility of testing sera without pre-treatment and automatic and instrument-mediated revealing, that makes it appropriate for large-scale screenings of affected pig farms in endemic regions or for monitoring plans in PEDV-free areas. Highlights: A monoclonal antibodies (MAbs)-based competitive ELISA for detecting antibodies against PEDV was developed and validated. The diagnostic performance of the test was evaluated by ROC analysis using a panel of 829 known sera. The ELISA showed excellent diagnostic performance and discriminatory power.